2007
DOI: 10.1590/s0100-879x2006005000190
|View full text |Cite
|
Sign up to set email alerts
|

Association between the -174 G/C promoter polymorphism of the interleukin-6 gene and cardiovascular disease risk factors in Brazilian older women

Abstract: In worldwide studies, interleukin-6 (IL-6) is implicated in age-related disturbances. The aim of the present report was to determine the possible association of IL-6 -174 C/G promoter polymorphism with the cytokine profile as well as with the presence of selected cardiovascular risk features. This was a cross-sectional study on Brazilian women aged 60 years or older. A sample of 193 subjects was investigated for impaired glucose regulation, diabetes, hypertension, and dyslipidemia. Genotyping was done by direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 40 publications
1
27
0
3
Order By: Relevance
“…The protective action is triggered by physiological stimuli such as the shear stress exerted by blood flow against endothelial cells, which results in basal production of NO, maintaining the blood vessel in a constant state of vasodilation. 5,10 Nitric oxide plays an active part in many of the protective functions performed by the intact endothelium and, in conjunction with Prostacyclin-2 (PGI-2), it exerts a potent antiatherogenic effect, preventing platelet adhesion and aggregation. 13 Palmer et al conducted an in vivo study that clearly demonstrated how NO and ET-1, which have opposing effects, regulate vascular tone and arterial blood pressure.…”
Section: Endothelial Functionmentioning
confidence: 99%
See 4 more Smart Citations
“…The protective action is triggered by physiological stimuli such as the shear stress exerted by blood flow against endothelial cells, which results in basal production of NO, maintaining the blood vessel in a constant state of vasodilation. 5,10 Nitric oxide plays an active part in many of the protective functions performed by the intact endothelium and, in conjunction with Prostacyclin-2 (PGI-2), it exerts a potent antiatherogenic effect, preventing platelet adhesion and aggregation. 13 Palmer et al conducted an in vivo study that clearly demonstrated how NO and ET-1, which have opposing effects, regulate vascular tone and arterial blood pressure.…”
Section: Endothelial Functionmentioning
confidence: 99%
“…33 Since IL-6 is involved in a series of immunological activities, in particular synthesis of acute phase substances in the liver, it is an important inflammatory marker, because it is involved in metabolic regulation of CRP. 10 Both IL-6 and its receptor (gp130), are widely expressed during an inflammatory reaction, leading to undesirable effects on several organs. 10 Normally IL-6 is expressed in low concentrations, except during infections, traumas or in the presence of other stressing factors.…”
Section: Function and Inflammationmentioning
confidence: 99%
See 3 more Smart Citations